2022
DOI: 10.4315/jfp-22-178
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline-Resistant, Third-Generation Cephalosporin–Resistant, and Extended-Spectrum β-Lactamase–Producing Escherichia coli in a Beef Cow-Calf Production System

Abstract: Cow-calf production plays a significant role in the beef production chain. However, it is not typically monitored for antimicrobial resistance (AMR). We determined the baseline level of bacterial AMR in pre-weaned calves prior to feedlot entry and evaluated wheat grazing and age effects on their occurrence. Two grazing experiments, with 16 cow-calf pairs each, were conducted on tall fescue or wheat. Fecal samples were cultured for the detection of tetracycline (TETr )-, 3rd generation cephalosporin (3GCr )-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 32 publications
4
8
1
Order By: Relevance
“…Globally the prevalence of ESBL positive samples from calves range from 13-30% in the USA to 30% in Europe (Agga et al, 2022;Haenni et al, 2014b;Salaheen et al, 2019). In our study those ACBL producing E. coli isolated were putative chromosomal mediated, with the mutations found in the promoter region of the ampC gene previously described in E. coli isolates from both calves and adult cattle (Alzayn et al, 2020;Hordijk et al, 2013b;Santiago, 2019).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Globally the prevalence of ESBL positive samples from calves range from 13-30% in the USA to 30% in Europe (Agga et al, 2022;Haenni et al, 2014b;Salaheen et al, 2019). In our study those ACBL producing E. coli isolated were putative chromosomal mediated, with the mutations found in the promoter region of the ampC gene previously described in E. coli isolates from both calves and adult cattle (Alzayn et al, 2020;Hordijk et al, 2013b;Santiago, 2019).…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have found that the prevalence of antimicrobial resistant E. coli and their genes is greater in calves compared with adult cattle (Agga et al, 2022;Geser et al, 2012;Khachatryan Artashes et al, 2004;Weber et al, 2021). Although our study did not directly compare calves with adult cattle, MDR E. coli have rarely been isolated from New Zealand adult cattle (Burgess et al, 2021a;Burgess et al, 2021b;Collis et al, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Much like the species distribution, wheat grazing affected the distribution of the tet and MLS B genes by either increasing [tet(O), erm(B)] or decreasing [tet(L), msr(C)] their prevalence. Wheat grazing had a similar effect on resistance gene distribution among TET r and third generation cephalosporin resistant E. coli isolates characterized from the same cow-calf populations (Agga et al, 2022b). These findings suggest that wheat grazing significantly affects the resistance gene distribution by favoring the expansion of bacterial population carrying certain genes, while suppressing bacterial population carrying other genes despite conferring the same phenotypic resistance.…”
Section: Discussionmentioning
confidence: 63%
“…The mechanisms and benefits to calves grazing on wheat need to be explored for the mitigation of AMR, especially because calves go to feedlot for beef production, with food safety implication. However, we previously reported from the same cow-calf population that wheat grazing had no effect on the prevalence and concentration of TET r E. coli (Agga et al, 2022b) suggesting the differential effect of wheat grazing on Grampositive and Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 71%
“…coli could be due to New Zealand dairy farms being low users of antibiotics, particularly third and fourth generation cephalosporins [61, 62, 75]. Globally the prevalence of ESBL positive samples from calves range from 13–30 % in the USA to 30 % in Europe [71, 73, 76]. In our study those ACBL producing E.…”
Section: Discussionmentioning
confidence: 89%